THE IMPACTS OF UNPLANNED PREGNANCY ON ADOLESCENCE: A LITERATURE REVIEW - Hastuti, Puji; Juwita, Bening; Yunitasari, Esty (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Pregnant adolescents (age 10-19) are at risk for complications of pregnancy and childbirth such as eclampsia and puerperal endometritis, which is one of the major causes of maternal death in the world. Unsafe abortions pose the same health risks (WHO 2018). Unwanted pregnancies reported by women in the 15-19 age group are twice as high (16%) as in the 20-24 age group (8%) (IDHS, 2017). Objective: The literature review’s purpose was to analyse the impact of pregnancy on adolescents through scientific evidence from research results of several researchers. Methods: The study was conducted with a literature review design, where the data used were secondary data from articles that examined adolescents with problems with unplanned pregnancies or adolescents who experienced early marriage due to unplanned pregnancies. The framework used to search for articles used PICOS. The article was limited to empirical studies of the last 5 years. Search through Google Scholar database, e-resource, Science Direct and Pubmed. Keywords and Boolean operators used were impacts and unplanned pregnancy and teen. Keywords adjusted to Medical Subject Heading (MeSH), obtained a sample of 22 reviewed articles. Result: The search results obtained 22 articles and it had similarities, namely 8 articles discussing physical impacts, 11 articles discussing psychological impacts, 15 articles discussing social impacts and 7 articles discussing economic impacts. Through this review, the physical impact results were premature birth, anemia and hypertension during pregnancy, attempted abortion, psychological impact in the form of feelings of fear, depression, guilt and disappointment with oneself, social impact in the form of dropping out of school, community stigma because it was considered a problem group, not getting support from the environment and the economic impact was difficulty finding work so that it was difficult to meet daily needs. Conclusion: Adolescents who decide to maintain their pregnancy is the best decision, but the significant impact that adolescents will experience makes them at high risk for physical disorders.